2021
DOI: 10.1371/journal.pone.0254548
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic monitoring of adalimumab at non-trough levels in patients with inflammatory bowel disease

Abstract: Adalimumab (ADA) trough level and anti-ADA antibody (AAA) positivity influence mucosal healing and loss of response in patients with inflammatory bowel disease (IBD). In this study, we clarified the correlation between ADA monitoring, including non-trough level, and real-world IBD clinical outcomes. This retrospective, observational, single-center study involved patients with ulcerative colitis (19) and Crohn’s disease (33) treated with ADA from January 2007 to August 2018. Serum ADA and AAA levels were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…It is hoped that IFX and GLM will be investigated based on accumulated results in future cases. It was also reported that the neutrophil to lymphocyte ratio is useful for predicting the efficacy of anti-TNF-α antibody drugs [ 20 ]. In this study, leukocyte differential analysis was performed, but no significant differences were shown for any of the variables, which may be due to the small sample size and differences in endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…It is hoped that IFX and GLM will be investigated based on accumulated results in future cases. It was also reported that the neutrophil to lymphocyte ratio is useful for predicting the efficacy of anti-TNF-α antibody drugs [ 20 ]. In this study, leukocyte differential analysis was performed, but no significant differences were shown for any of the variables, which may be due to the small sample size and differences in endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data suggest that serum adalimumab concentrations are stable in the first 9 days after injection and can reasonably predict therapeutic trough drug levels, potentially allowing for earlier decision-making based on non-trough adalimumab levels [51,52]. One study by Kato et al found serum ADA levels are predictive of clinical outcomes regardless of trough timing [53]. This may be helpful for patients on more frequent dosing of adalimumab, while the timing of drug levels may be more important to make for patients requiring longer follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…TDM strategies are increasingly used by clinicians and allow for personalized dose modification based on patients' clinical data, measurement of biologic trough levels, and presence of antidrug antibodies. [9][10][11][12][13][14] TDM strategies in CD are traditionally classified as either "reactive" or "proactive": Reactive TDM is the measurement of biologic concentration and antibodies at the time of symptomatic recurrence, and proactive TDM is the scheduled monitoring of serum drug concentrations to maintain a pre-specified range regardless of symptoms. Evidence shows that proactive TDM strategies applied during biologic maintenance can improve clinical outcomes and reduce CD-related hospitalizations and surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) is a common strategy to reverse/prevent loss of IFX response by optimizing PK. TDM strategies are increasingly used by clinicians and allow for personalized dose modification based on patients' clinical data, measurement of biologic trough levels, and presence of antidrug antibodies 9–14 . TDM strategies in CD are traditionally classified as either “reactive” or “proactive”: Reactive TDM is the measurement of biologic concentration and antibodies at the time of symptomatic recurrence, and proactive TDM is the scheduled monitoring of serum drug concentrations to maintain a pre‐specified range regardless of symptoms.…”
Section: Introductionmentioning
confidence: 99%